Introducing Bibliotherapy in Public Libraries of Jaffna district: an Exploratory Study - Arulanantham, S.; Navaneethakrishnan, S. (Journal of the University Librarians Association, 2013)
This study investigates the role of the public library sector of Jaffna district in Northern Sri Lanka towards providing bibliotherapy as a service to the waraffected people seeking help in solving their problems. Using Survey research method, collected data was analyzed to find out the awareness of the concept, acceptance of bibliotherapy as method of treatment, existence and suitability of bibliotherapy in public libraries and the attitude of the librarians to be a bibliotherapist. The study suggests the possibility of implementing bibliotherapy in public libraries of Jaffna district with the support of health authorities.
Keywords: Bibliotherapy; Bibliotherapy-Public libraries; Bibliotherapy - Library services; Reading therapy